Phenotypic classification of von Willebrand disease (Hematology Meeting Reports, 2009)
Von Willebrand disease (VWD) is caused by quantitative and/or qualitative defects of the von Willebrand factor (VWF), a multimeric high molecular weight glycoprotein. Typically it affects the primary hemostatic system, which is reflected by a mucocutaneous bleeding tendency simulating a platelet function defect. VWD is the most common inherited coagulation disorder. The current classification comprises the main types 1, 2 and 3. The qualitative type 2 variants are differentiated into the subtypes 2A, 2B, 2M and 2M. Among these, type 2A is very heterogeneous, consisting of several phenotypically different disease entities with the diagnostic hallmark of a loss of the large multimers. Up to now, the quantitative type 1 variants were considered the most prevalent with frequencies of 70% to 80%, compared to type 2 (15-25%) and type 3 (